Sustainable Reporting: Upaya Korporasi Mengevaluasi Corporate Social Responsibility - Tedjasuksmana, Budianto (Jurnal Akuntansi Kontemporer, 2011)
Any discussion of social responsibilities reporting necessarily needs to consider what the responsibilities of organizations are. Are businesses responsible to their direct owners( shareholders) alone, or do they owe a duty to the wider community in which they operate? Certainly, many organizations are making public statements to the effect that they consider that they do have responsibilities to parties other than just the shareholders. A .firm should voluntarily discloses information publicly about its social and environmental performance that implies the managers are acknowledging that they are accountable to abroad group of stakeholders in relation not to only their financial performance, but also their social and environmental performance. Those environmental aspects should be described in o lot of progress in their social publicly responsibilities reporting, hoping that all shareholders know completely the whole position and financial performance, risks, business prospects and corporate sustainability. The accountability of corporate must disclose their socio economic environmental accounting as a broader of Corporate Social Responsibility (CSR), which contain of social maping, that shows harmonization of goals between corporate and peoples.